Gravity assisted continuous flow peritoneal dialysis (CFPD) in children with acute kidney injury - Nourse, Peter (Department of Paediatrics and Child Health, 2026)
Background: Peritoneal dialysis (PD) has long been a mainstay of acute kidney injury (AKI) management in children of all ages, and it remains the most commonly used modality in low-income regions, where continuous kidney replacement therapy (CKRT) is not widely available. Compared to extracorporeal therapies, PD has lower clearance as well as lower and less precise fluid removal. We previously demonstrated increased ultrafiltration and clearances using continuous flow peritoneal dialysis (CFPD) in children with AKI, however the technique described required expensive high-volume CKRT pumps to circulate fluid, as well as high level technical expertise, limiting its utility in resource-constrained settings. Identifying safe, effective and low-cost techniques for CFPD may improve access to dialysis for children with AKI in low-resource settings.